EVALUATING THE EFFECTIVENESS OF THE GURU PENGGERAK PROGRAM: A GUIDANCE AND COUNSELING APPROACH TO TEACHER PROFESSIONAL DEVELOPMENT AND EDUCATIONAL TRANSFORMATION - Abdillah, Arif Taufiq Dani; Setianingsig, Eka Sari (EDUCATIONE, 2025)
Evaluation is one of the methods used to assess the success of a process in achieving its initial objectives. Evaluation through a guidance and counseling approach involves the collection of information (data) to determine effectiveness (implementation and achievement) based on three evaluation components: Understanding, Conform, and Action (UCA). This approach is applied in evaluating the Program Pendidikan Guru Penggerak (PPGP) in Banten Province by the Balai Guru Penggerak (BGP) Banten, using an evaluation mechanism that aligns with the principles of Guidance and Counseling (BK). The evaluation results serve as a benchmark for the success of the Guru Penggerak Program (PGP). The findings of this study indicate that the application of evaluation using the guidance and counseling approach in the implementation of the Guru Penggerak Program is more easily applicable. By utilizing the three evaluation components, the level of satisfaction regarding the program’s implementation and outcomes, the competencies acquired, as well as the planned actions and decision-making processes of Guru Penggerak participants, can be effectively identified.